1994
DOI: 10.1902/jop.1994.65.5.393
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Ulcerative Periodontitis: A Marker for Immune Deterioration and a Predictor for the Diagnosis of AIDS

Abstract: A multitude of oral lesions have been described in individuals infected with the human immunodeficiency virus (HIV). Few studies have attempted to correlate specific oral findings with immune status and HIV disease progression in the population reflecting the demographic profile of this epidemic. A prospective study was conducted among 700 ambulatory HIV-infected individuals seeking dental care between July 1, 1988 and June 30, 1992. Patients entered the study when they first applied for care and were followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
3
10

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(90 citation statements)
references
References 11 publications
7
70
3
10
Order By: Relevance
“…bastante por encima, ya que los investigadores informan cifras cercanas al 40%, explicables por la facilidad de acceso a los servicios de salud en dichos países. En cuanto al tipo de enfermedad más prevalente, la candidosis oral, se confirma lo encontrado por De igual manera, las gingivitis-periodontitis asociadas con el VIH y la leucoplasia vellosa se comportan de manera parecida, lo cual seiiala su importancia como trazadoras de infección VIH y como predictoras de desarrollo de sida (15,16,28,(47)(48)(49)(50)(51). Sería interesante que en los estudios futuros se contara con la confirmación histológica de las lesiones leucoplásicas, tal como lo recomiendan ciertos autores (10, [36][37][38][39][40], ya que algunas de ellas pudieran corresponder a candidosis hiperplásica, liquen plano o lesiones penfigoides, semejanzas que sesgarian los resultados (52,53).…”
Section: Discussionunclassified
“…bastante por encima, ya que los investigadores informan cifras cercanas al 40%, explicables por la facilidad de acceso a los servicios de salud en dichos países. En cuanto al tipo de enfermedad más prevalente, la candidosis oral, se confirma lo encontrado por De igual manera, las gingivitis-periodontitis asociadas con el VIH y la leucoplasia vellosa se comportan de manera parecida, lo cual seiiala su importancia como trazadoras de infección VIH y como predictoras de desarrollo de sida (15,16,28,(47)(48)(49)(50)(51). Sería interesante que en los estudios futuros se contara con la confirmación histológica de las lesiones leucoplásicas, tal como lo recomiendan ciertos autores (10, [36][37][38][39][40], ya que algunas de ellas pudieran corresponder a candidosis hiperplásica, liquen plano o lesiones penfigoides, semejanzas que sesgarian los resultados (52,53).…”
Section: Discussionunclassified
“…A subsequent study [46] proved that chronic periodontitis is a risk factor for HIV patient suffering from cancer. Immunological studies showed significantly decreased T cells in gingival tissues of HIV-positive patients [47] . Modifications were also noted in local immune responses, such as increased inf lammatory mediators and polymorphonuclear leukocyte accumulation.…”
Section: Effects Of Oral Microorganisms On Tumor Occurrence Of Hivposmentioning
confidence: 99%
“…It can take two forms: the rapid and severe condition called necrotizing ulcerative periodontitis (NUP), (Glick et al, 1994) and its associated and possibly precursor condition called linear gingival erythema (LGE), (Grbic et al, 1995). The presenting clinical features of these diseases often differ from those in non-HIV-infected persons in that unlike for non-HIV-related periodontal disease LGE and NUP often occur in clean mouths where there is very little plaque or calculus to account for the gingivitis.…”
Section: Periodontal Diseasementioning
confidence: 99%